Pengembangan Hubungan Pasangan dan Mediator dalam Proses Pengambilan Keputusan Menikah pada Penjajagan Pranikah Ta’aruf - Aini Fathuningtyas, Maghfira; Naryoso, Agus (Interaksi Online, 2021)
This research is written to discuss romantic relationship ta'aruf in the process of decision-making marriage who have communication constraints that inhibit the escalation process of relationships from strangers into intimates. Ta'aruf has its own relationship development process in order to create a positive, optimistic, and open relationship in the division of roles. The short process and the presence of a mediator who helps establishing communication between partners make the process of relationship development to foster love become hampered, as well as the emergence of conflict between the two parties. This study aims to determine how couples experience in the process of developing relationships ta'aruf for decision-making marriage or not through phenomenological approach. This research uses the foundation of Relationship Development Stages in a Committed Relationship, the concept of Self Disclosure, Relational Dialectic Theory. The data collection technique used is in-depth interview with the research subject of four ta'aruf couples consisting of two couples who were successfully married and two couples who failed to marry from the ta'aruf process.The results of this study revealed romantic relationship in ta'aruf couples have their own peculiarities because in the development of the relationship they refer to the teachings of Islam which limit the overflow of excessive love and love before marriage. There is a mediator who is trusted by ta'aruf couples as a bridge of communication where communication competence is relied on in guiding, mediating the ta'aruf couples when faced with conflicts. Although in the process the mediator inhibits the exclusion of the couples’ relationship ta'aruf, but the informants respond to this limitation with a positive attitude. In the process of introducing committed romantic relationship to the ta'aruf couples, it is observed at the stage of contact, involvement, intimacy. The decision-making for ta’aruf couples to marry or not is based on alternative choices that are considered good and bad by individuals and referral groups.